2022
DOI: 10.1186/s12889-022-13051-w
|View full text |Cite
|
Sign up to set email alerts
|

Survival of eight LLIN brands 6, 12, 24 and 36 months after a mass distribution campaign in rural and urban settings in Senegal

Abstract: Background Long lasting insecticidal nets (LLIN) are one of the core components of global malaria prevention and control. The lifespan of LLIN varies widely depending on the population or environment, and randomized studies are required to compare LLIN inaccording to arbitrary thresholds households under different field conditions. This study investigated survival of different LLIN brands in Senegal. Methods Ten thousand six hundre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This relationship was measured by the median index and revealed that more than half of Olyset Net ® type LLINs were in poor condition compared to Dawa Plus ® 2.0; all thirty Olyset Net ® sampled at 36 months had lost their physical barrier. This result corroborates those found recently in Senegal [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This relationship was measured by the median index and revealed that more than half of Olyset Net ® type LLINs were in poor condition compared to Dawa Plus ® 2.0; all thirty Olyset Net ® sampled at 36 months had lost their physical barrier. This result corroborates those found recently in Senegal [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…The low retention rate of the LLINs deployed in our study could be explained by the mass distribution campaign implemented in the area during the fifth semester or by the gifting of nets to relatives or friends observed during the first six months. A study has shown that, in Senegal, loss due to moving away is the most important during the first month post-distribution [ 39 ]. However other attrition factors related the loss and deterioration of LLINs are observed in the field during surveys.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary, results by Talipouo et al [ 5 ] in Yaoundé (Cameroon) reported more than half of the LLINs in use in good condition. Diouf et al [ 48 ] concluded that the rapid degradation of mosquito nets would largely depends on their improper use (washing, drying, threading), which also depends on the year of acquisition. Messages about LLIN washing procedures should be disseminated in the locality to help maintain their integrity, effectiveness and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The low proportion of bed net ownership reported in this study could be explained by the fact that the study was conducted several years after a mass LLIN campaign where the majority of the distributed nets are likely no longer being used or functional. Indeed, while LLIN are expected to last at least 3 years, studies on LLIN durability, revealed that under routine conditions LLIN can lose effectiveness because they are physically damaged, repurposed or discarded [54,55]. Routine distribution of LLINs is also carried out at community level and in health facilities [14].…”
Section: Discussionmentioning
confidence: 99%